One-step Real-time Food Quality Analysis by Simultaneous DSC–FTIR Microspectroscopy. Issue 2 (25th January 2016) - Lin, Shan-Yang; Lin, Chih-Cheng
Abstract : This review discusses an analytical technique that combines differential scanning calorimetry and Fourier-transform infrared (DSC–FTIR) microspectroscopy, which simulates the accelerated stability test and detects decomposition products simultaneously in real time. We show that the DSC–FTIR technique is a fast, simple and powerful analytical tool with applications in food sciences. This technique has been applied successfully to the simultaneous investigation of: encapsulated squid oil stability; the dehydration and intramolecular condensation of sweetener (aspartame); the dehydration, rehydration and solidification of trehalose; and online monitoring of the Maillard reaction for glucose (Glc)/asparagine (Asn) in the solid state. This technique delivers rapid and appropriate interpretations with food science applications.